A New Civilization Represented in Leigh Whannel’s Upgrade (2018) - Amir Mahmudin (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2021)
This research intends to analyze: (1) new civilizations in technology advancement in Upgrade 2018 and (2) technical improvements based on artificial intelligence in Upgrade 2018. Upgrade 2018 by leigh whannell was studied using qualitative approaches in this study. Reading, recognizing, categorizing, and choosing are some of the data collection methods used in this study. Displaying, explaining, and interpreting data are the methods used to analyze the data. The researcher uses Julian Huxley's transhumanism to further investigate a new civilization in the Upgrade 2018. Transhumanism is a philosophy that claims that with the assistance of technology, people can surpass their boundaries, but that technology will ultimately rule world civilization. This is comparable to what happened in Leigh Wannell's Upgrade 2018. Gray, a skeptic of technology, is used as an experimental material in the union of people and technology in one body, and the notion of transhumanism becomes a reality in the Upgrade 2018. Aside from the union of people and technology in the Upgrade 2018, the influence of technology proliferation everywhere and human work being replaced by technology is also an essential component in the new civilization in the Upgrade 2018.